Fasting induces astroglial plasticity in the olfactory bulb glomeruli of rats. Issue 4 (11th December 2017) - Daumas‐Meyer, Virginie; Champeil‐Potokar, Gaëlle; Chaumontet, Catherine; Dahirel, Patrice; Papillon, Catherine; Congar, Patrice; Denis, Isabelle
Abstract: The detection of food odors by the olfactory system, which plays a key role in regulating food intake and elaborating the hedonic value of food, is reciprocally influenced by the metabolic state. Fasting increases olfactory performance, notably by increasing the activity of olfactory bulb (OB) neurons. The glutamatergic synapses between olfactory sensory neurons and mitral cells in the OB glomeruli are regulated by astrocytes, periglomerular neurons, and centrifugal afferents. We compared the expansion of astroglial processes by quantifying GFAP‐labeled areas in fed and fasted rats to see whether OB glomerular astrocytes are involved in the metabolic sensing and adaptation of the olfactory system. Glomerular astroglial spreading was much greater in all OB regions of rats fasted for 17 hr than in controls. Intra‐peritoneal administration of the anorexigenic peptide PYY3‐36 or glucose in 17 hr‐fasted rats respectively decreased their food intake or restored their glycemia, and reversed the fasting‐induced astroglial spreading. Direct application of the orexigenic peptides ghrelin or NPY to OB slices increased astroglial spreading, whereas PYY3‐36 resulted in astroglial retraction, in agreement with the in vivo effects of fasting and satiety on glomerular astrocytes. Thus the morphological plasticity of OB glomerular astrocytes depends on the metabolic state of the rats and is influenced by peptides that regulate food intake. This plasticity may be part of the mechanism by which the olfactory system adapts to food intake. Main Points: Fasting induces astroglial spreading in rat OB glomeruli. Restoration of glycemia or the satietogenic PYY3‐36 (but not leptin) reverse this morphological plasticity. Orexigenic ghrelin and NPY induce the astroglial spreading.